Sport, culture and society an introduction - Jarvie, Grant 1955-; Thornton, James; Mackie, Hector (London Routledge, Taylor & Francis Group, an Informa Business, 2018)
Sport, Culture and Society : An introduction, 3rd Edition now in a fully revised, updated and expanded edition, this critical, challenging and comprehensive textbook introduces the study of sport, culture and society. International in scope, it challenges us to reactivate an audacious spirit of activism through sport. Full of contemporary examples, it places sport at the heart of the analysis and introduces the reader to every core topic and emerging area in the study of sport and society, including: the history and politics of sport; sport, gender and sexuality; sport, disability and advocacy; sport, race and racism; sport, violence and crime; sport and health; sport, globalisation and democracy; sport, media and cultural relations; sport and the environment; sporting cities and mega-events; sport, poverty and development. Each chapter includes a wealth of useful features, including Sport in Focus case studies, chapter summaries, guides to further reading, revision questions, practical projects, definitions of key concepts and weblinks. Additional teaching and learning resources -- including a testbank, resource list and glossary -- are available on a companion website. Sport, Culture and Society is the most broad-ranging, in-depth and thoughtful introduction to the sociocultural analysis of sport currently available and sets a new agenda for the discipline. It is essential reading for all students with an interest in sport.
Introduction -- PART I: The Broader Context : 1. Sport, Theory and the Problem of Values 2. Sport, History and Social Change 3. Sport, Economics and Wealth 4. Sport, Development and Peace 5. Sport, Politics and Culture -- PART II: Global Sport and Community : 6. Global Sport in a Deglobalising World? 7. Sport, Law and Governance 8. Sport and Community 9. Internationalism, Reconciliation and Sport in the Making of Nations 10. Sport, Media and Technology 11. Sport, Social Capital and Civil Society 12. Sport and Education -- PART III: Sport and Contemporary Social Issues : 13. Sport and the Environment 14. Sport and Racism 15. Sport, Violence and Crime 16. Sport, Religion and Spirituality 17. Sport, Gender and Sexuality 18. Sport and Health 19. Sport and Disability 20. Sport, Cities, the Olympics and Major Sporting Events 21. Sport, Lifestyles and Alternatives 22. Sport, Gambling and Corruption 23. Sport, Poverty and Homelessness -- PART IV: Sport as a Resource of Hope and the Politics of the Possible : 24. Sport, Social Movements and Protest 25. Sport, Cultural Relations and Damned Nations 26. Sport, Human Rights and Public Action 27. Sport for Social Change 28. Sport, Advocacy the Public Intellectuals -- Conclusion: Theses on Sport, Culture and Society -- Bibliography
Includes bibliographical references (pages 522-544) and index.
Keywords: Sports -- Social aspects